Beyond Numbers: A Study of Non-Monetary Values in Accounting Through the Lens of Sedekah Bumi Tradition in Yogyakarta - Fatma Dian Andriani; Marko S. Hermawan (Green Publisher Indonesia, 2024)
Cultural accounting, a nuanced exploration of the interplay be-tween accounting practices and cultural dynamics, takes center stage in this empirical study. The research endeavors to present a thorough overview encompassing theoretical foundations, meth-odological approaches, and implications for accounting practices and policies. Delving into theoretical underpinnings, the study aligns cultural accounting with disciplines such as sociology, anthropology, and critical theory, unraveling intricate cultural dimensions across national, organizational, and individual realms that shape accounting practices. Methodologically, a spotlight is cast on qualitative techniques like ethnography, in-terviews, and case studies, underscoring their contribution to the depth and richness of cultural accounting research. Furthermore, the study probes the impact of cultural accounting on diverse aspects of accounting practices and policies, particularly explor-ing its manifestation in the context of almsgiving culture. Cul-minating in a critical analysis, the research not only identifies gaps in the existing literature but also sets the stage for future research trajectories. This succinct yet comprehensive explora-tion serves as a catalyst for advancing cultural accounting dis-course, offering insights poised to influence and inform adaptive accounting practices in our dynamically evolving global milieu.